Exploration of a low-cost radar and image processing - Zhang, Xingwen (2019)
The origin for radio wave principles can date back to19th century. During 1886 to 1888, German scientist Heinrich Hertz found the electromagnetic waves, including radio waves do exist. This kind of signal can transmit through various types of mediums, and reflection will take place when the electromagnetic waves are blocked by metal surfaces. In general, the characteristics such as being reflected, refracted and polarized for radio waves are quite like that of the visible lights, which can be further supported by wave–particle duality of light by Albert Einstein in 1905. After that, World War II plays an important role as the catalyst for its development, and the RADAR (Radio Detection and Ranging) technology was officially invented in 1930, which marks the milestone in radar history. During that time, the application for radar technique is generally only for military purpose. However, during the next century, Radar technique is also applied to many civilian fields. The main aim of this project is to explore one specific aspect of radar technique, specifically for detection and image processing. To implement the functionality, a simple but typical radar tool kit is selected to simulate the transmitting and receiving stages as a two-antenna communication channel. In order to extract and further process the acquired signal, the popular software kit MATLAB is introduced, and plays an important role in helping us to filter the noise, restore the actual shape and distance information for the target object. The analysis results for this project lay a solid foundation for the development of in-wall detection, such as detection of pipelines before electric line installation to ensure safety. The background information and details of how the experiments are conducted are illustrated in detail in the following section of this report. Key pieces of the coding are also included and explained in sequence.